Secular trends in infant mortality by age-group and avoidable components in the State of São Paulo, 1996-2012 - Kelsy Catherina Nema Areco; Tulio Konstantyner; José Augusto de Aguiar Carrazedo Taddei
Abstract Objective: To describe trends and composition of infant mortality rate in the State of São Paulo, from 1996 to 2012. Methods: An ecological study was conducted, based on official secondary data of births and infant deaths of residents in São Paulo, from 1996 to 2012. The infant mortality rate was calculated by the direct method and was analyzed by graphs and polynomial regression models for age groups (early neonatal, late neonatal and post-neonatal) and for groups of avoidable causes of death. Results: The mortality rate in the State of São Paulo tended to fall, ranging from 22.5 to 11.5 per thousand live births. Half of the infant deaths occurred in the early neonatal group. The proportion of avoidable infant deaths varied from 76.0 to 68.7%. The deaths which were avoidable by adequate attention to women during pregnancy and childbirth and newborn care accounted for 54% of infant deaths throughout the period. Conclusions: The mortality rate levels are still far from those in developed countries, which highlight the need to prioritize access and quality of healthcare services during pregnancy, childbirth and newborn care, especially in the first week of life, aiming at achieving standards of infant mortality similar to those of developed societies.